Parigolade le journal des parigolos - Berroyer, Jackie 1946-; Delépine, Benoît 1958-; Gourio, Jean-Marie 1956-; Mounet, Pascal (Le Village, 1989)
Journal pseudo satirique, créé à l'époque en réponse au très moyen 'le hérisson' (www.graphzines.net)
Offsetdruck
Keywords: Graphzine